Análise crítica da branquitude a partir de uma interlocução com a Psicologia Social - Henriques, Luciana Maciel (2018)
Taking as an analyze the term whiteness, this master’s thesis emerges from a research about racial relations with the performance of the social psychologist, in a fight against racism. It is a research that understands whiteness as a white hegemony, which potentiates and reproduces racism in Brazil in the 21st century. This hegemony arises based in a social construction of the hierarchy of races, created by Europeans in the colonialism. Starting from the concept of hegemony, as well as the exploration of researches about race, racism and racial relations, this analysis is critically examined through a review of the history of Brazil regarding racial relations, as well as the consolidation of Psychology through studies about race in Brazil. The possibilities of interlocution between Social Psychology and these studies are observed, making it necessary to assume a participative position in the studies and in the works regarding to the racial relations and critical studies of the whiteness, as well as the active stance in the fight against social inequalities in Brazil. It is proposed to observe the possibility of recognition in a position of reflection and problematization, focusing the critique of whiteness as an opportunity for the deconstruction of white hegemony in Brazilian society.